Cover - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
Comparison of Embankment Reinforcement Requirements with Geotextile on Soft Soil with 2D and 3D Slope Stability Analysis Methods Nur Arfiati Shoffiana, Yudhi Lastiasih & Trihanyndio Rendy Satrya Evaluation of Smart Mobility Indicators in Responding COVID-19 Pandemic in Indonesia Shanty Y. Rachmat & Ganesha G. Mangkoesoebroto Geotechnical Mapping for Soil Physical and Mechanical Parameters and Hard Soil Depth in Badung Regency Zefira Wisna Maulidha, Trihanyndio Rendy Satrya & Yudhi Lastiasih The Physical Integration of Smart Transportation Characteristics of Suroboyo Bus and the Feeder Cindy Nur Aziza Rahman, Eko Budi Santoso & Siti Nurlaela The Adequacy of Public Bus Fleet During the Covid-19 Pandemic (Case of The Transjakarta Corridor 1 DKI Jakarta, Indonesia) Amanda Dian W.Kusumawardani, Ibnu Syabri, Fika Novitasari & Naya C. Drestalita